IP Geolocation based on identification routers and local delay distribution similarity. (27th July 2018) - Zhao, Fan; Luo, Xiangyang; Gan, Yong; Zu, Shuodi; Cheng, Qingfeng; Liu, Fenlin
Summary: IP geolocation is usually used in fog computing to avoid high latency and discriminate malicious requests by judging the location of users. Existing delay measurement‐based IP geolocation approaches are not applicable to the network that has hierarchical topology and weak connectivity, and the precision of the classical Street‐Level Geolocation (SLG) method will decrease dramatically when the common routers are anonymous. In this paper, an IP geolocation method based on identification routers and local delay distribution similarity is proposed. The target IP's location at city‐level is firstly derived by matching its routing path with the identification routers that only forward packets to the same city. After that, the target IP's local delay between the nearest common router and the target IP is gathered, and the landmarks' are obtained at the same time. Finally, the location of the landmark that has the most similar local delay distribution with the target IP is taken as the geolocation result. Theoretical analysis and experimental results show that the proposed method can derive reliably geolocation results at city‐level for the target IP in the network with hierarchical architecture. Moreover, the geolocation accuracy of classical SLG method is improved obviously when the common routers are anonymous.